Accounting and Distributive Justice. - Flower, John (Routledge studies in accounting., 2010)
Challenges the basic assumptions on which the practice of financial reporting is based. This title uses the stakeholder theory of the firm to show that companies have a responsibility to achieve distributive justice, and the company's accounts could play an important role in fulfilling this responsibility.